Problem-based learning in radiology achieves similar results in classroom and metaverse settings - Teodoro Rudolphi-Solero; Fernando Bajos-Ariza; Rocío Lorenzo-Álvarez; Dolores Domínguez-Pinos; Miguel José Ruiz-Gómez; Francisco Sendra-Portero (Insights into Imaging)
Abstract Objectives The metaverse (MV) is a simulated virtual world enabling simultaneous interaction and communication between students, teachers, and colleagues. This study compared a problem-based learning experience in radiology conducted face-to-face in real life (RL) and within the MV. Methods During a radiology clinical rotation, groups of approximately 25 sixth-year medical students participated over 2 years in real life and 2 years in the MV. Each group was divided into eight teams of 3–4 students, each assigned a radiological clinical case for study, presentation, and debate with classmates. Students evaluated other teams, assessed case difficulty, and completed a perception questionnaire. Results A total of 348 students participated in the real-life group and 342 in the MV group, with average teacher evaluation scores of 8.11 ± 1.15 and 7.97 ± 1.54, respectively, showing no significant differences (p = 0.883). No significant differences were found in peer evaluations or case difficulty assessments. Both groups reported positive experiences, with overall satisfaction scores out of 10 points being 7.91 ± 1.32 for RL and 7.54 ± 1.87 for the MV, without significant differences (p = 0.073). Conclusions Problem-based learning activities in radiology can be effectively conducted in the MV, yielding academic results and experiential perceptions comparable to RL. The MV presents a viable alternative to face-to-face learning when in-person problem-based learning activities are impractical or challenging. Critical relevance statement This study highlights the potential of the metaverse for effectively conducting radiology problem-based learning activities. It provides evidence for its viability as an alternative educational tool, particularly when face-to-face learning is not feasible. Key Points Radiology problem-based learning in the metaverse achieved academic results comparable to traditional real-life classroom settings. The metaverse offers unique learning advantages, including remote access, 24/7 availability, and teamwork opportunities. The metaverse provides an excellent problem-based learning alternative when in-person activities are impractical or impossible. Graphical Abstract